Fatty Acid and Cholesterol Composition, and Tissues Description of Fresh and Fried Red Snapper Fillet - Agoes Mardiono Jacoeb; Pipih Suptijah; Widyana Ayu Kristantina (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2015)
Red Snapper is a widely consumed fish. The aim of this research was to determine the fatty acid and the cholesterol composition and to observe the tissues description of fresh and fried red snapper fillet. The fatty acid composition was tested using Gas Chromatography (GC) and the cholesterol with Bohac test. Fresh red snapper had moisture and protein content about 79.31% and 16.30%, respectively. Meanwhile fried red snapper contained mosture and protein about 1.98% and 28.40%, respectively.The highest compound of saturated fatty acid on red snapper were myristic acid; while of monounsaturated fatty acid were palmitoleat acid (C16:1). Of the polyunsaturated fatty acids, linoleic acid (C18:2) was found dominantly. Frying increased the cholesterol content from 20 mg/100 g to 60 mg/100 g of tissue. Tissue structure of fresh red snapper was found in not compact form because of low quality meat, however more compact structure was found on fried flesh of red snapper. Keywords: Cholesterol, fatty acids, meat tissue, proximate, red snapper (L. argentimaculatus)